MODEL ISLAMIC OPERATIONAL PADA KOPERASI SYARIAH DI KABUPATEN BANJAR - Yetty Indrawati; Khuzaini; Syahrial Syaddiq (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Islamic Operational Model, Sharia Cooperatives, Sharia Principles, Banjar Regency, Sharia Contracts, Sharia Compliance, Islamic Governance. Sharia cooperatives are microfinance institutions that play a vital role in driving the community economy based on Islamic principles. In Banjar Regency, the existence of sharia cooperatives serves as an alternative economic vehicle based on the values of justice, togetherness, and the prohibition of usury, gharar, and maysir. However, in practice, various obstacles are still encountered, such as the low understanding of sharia contracts among administrators and a weak supervisory system for cooperative operations. An Islamic Operational Model is needed to ensure that all cooperative activities are carried out in accordance with sharia principles, transparently, and professionally. This model emphasizes the proper implementation of contracts such as mudharabah, musyarakah, murabahah, and ijarah and strengthens the role of the Sharia Supervisory Board in maintaining compliance with Islamic law. This study aims to analyze the implementation of sharia principles in cooperatives in Banjar Regency and formulate an effective operational model, appropriate to the socio-economic conditions of the local community. Through a normative legal approach and field studies, the research results are expected to become the basis for strengthening the governance of Islamic cooperatives that are just, sustainable, and support the economic development of the people in an Islamic manner.